Not a steamroller, a 3D process: Scientization at the Bank of England - Aurélien Goutsmedt; Francesco Sergi; François Claveau; Clément Fontan (Finance and Society)
This article investigates the scientization process in central banks, using the Bank of England (BoE) as a case study. Its main goal is to clarify the interactions and tensions among three dimensions of scientization: contributory, policymaking and legitimizing. To do so, we outline an ideal type of contributory scientization in central banks, whereby they become active contributors to science. The article derives empirically observable characteristics for this ideal type, regarding leadership and staff profiles, use of internal resources, composition of external networks, and publication and discursive outputs. The BoE is then contrasted to this ideal type of a central bank thoroughly involved in contributory scientization. The empirical material includes archives and interviews as well as three databases providing quantitative information from the 1970s to 2019. We find that the development of contributory scientization is strategically motivated, often generating tensions with policymaking and legitimizing dimensions. Our findings suggest that scientization in central banks is best understood as a three-dimensional, non-linear process, rather than a steamroller.